Formation-Evolutionary Mechanism Analysis and Impacts of Human Activities on the 20 August 2019 Clustered Debris Flows Event in Wenchuan County, Southwestern China - Li, Yu; Liu, Xing-nian; Gan, Bin-rui; Wang, Xie-kang; Yang, Xing-guo; Li, Hai-bo; Long, Xing-yu; Zhou, Jia-wen (Frontiers in Earth Science, 2021)
Characterized by large scale, high frequency, and strong destructiveness, debris flow has become the most noticeable geohazards throughout the world, especially in the mountainous areas of southwestern China. On August 20, 2019, large-scale heavy rainfall pummeled Wenchuan County, Sichuan Province, southwestern China, which resulted in a cluster of debris flows (the “8•20” clustered debris flows event), and caused considerable economic losses (approximately 3.4 billion RMB were lost) and heavy casualties (48,862 people were displaced, 16 people died and 22 people went missing). Based on field investigation, image data interpretation, mechanism analysis, and other methods, this study reveals the formation mechanism, dynamic evolutionary process, and impacts of human activities on the “8•20” clustered debris flows event. Results from a comprehensive analysis indicate that the occurrence of short-term, high-intensity rainfall and the excessive supply of solid material were the main factors that triggered this catastrophic event. With the debris flow flowing into the main river, this event presented an extremely apparent disaster chain effect. It is also found that improper site selection and inadequate design of human activities played a crucial role in the movement process of the debris flow that directly aggravated the losses. Finally, to improve debris flow prediction and prevention, some early warning and mitigation measures are discussed.